Strategi Penerapan E-Government Dalam Rangka Meningkatkan Pelayanan Publik Melalui E-Complaint (Studi Pada Dinas Perhubungan, Komunikasi Dan Informatika Pemerintah Kota Blitar) - Elga Goesman Vrtdiansyah Miftahul Hudha (Jurnal Administrasi Publik, 2016)
Abstract: Implementation of E-Government Strategy to Improve Public Services Through E-Complaint (Studies in the Department of Transportation, Communications and Information Technology Government of Blitar). One of the functions of e-Government in the public service through the Complaint Service Unit and the Information Society (ULPIM). Results of analysis showed that the strategy of implementation of e-government in improving public services through e-complain on Dishubkominfo Blitar is to establish the superstructure (policy), establishes the superstructure (the policy), the development of Apparatus Resources (SDA) The Government of Blitar, providing network infrastructure that is the provision of free Internet access, providing Internet access Government of Blitar and provision of Mail Server, providing Infrastructure Application System through the manufacturing sites across the Local Government Unit (SKPD) Government of Blitar, providing funding in connectedness with the handling of complaints and information and conduct the evaluation process also carried out by the department in order to provide assurance that the e-Gov can improve public services through e-complain Keywords: Strategy Implementation of E-Government, Public Services and E-Complaint Abstrak: Strategi Penerapan E-Government Dalam Rangka Meningkatkan Pelayanan Publik Melalui E-Complaint (Studi Pada Dinas Perhubungan, Komunikasi Dan Informatika Pemerintah Kota Blitar) Salah satu fungsinya e-Government dalam pelayanan publik melalui Unit Layanan Pengaduan dan Informasi Masyarakat (ULPIM). Hasil analisis dapat diketahui bahwa strategi penerapan e-government dalam meningkatkan pelayanan publik melalui e-complaint pada Dishubkominfo Blitar yaitu dengan menetapkan suprastruktur (kebijakan), menetapkan suprastruktur (kebijakan), pengembangan Sumber Daya Aparatur (SDA) Pemerintah Kota Blitar, menyediakan infrastruktur jaringan yaitu dengan penyediaan akses internet gratis, penyediaan akses Internet Pemerintah Kota Blitar dan penyediaan Mail Server, menyediakan Infrastruktur Sistem Aplikasi melalu pembuatan situs di seluruh Satuan Kerja Pemerintah Daerah (SKPD) Pemerintah Kota Blitar, menyediakan Pendanaan dalam keterhubungan dengan penanganan pengaduan dan informasi dan melakukan proses evaluasi juga dilakukan oleh dinas dalam rangka untuk memberikan jaminan bahwa e-Gov dapat meningkatkan pelayanan publik melalui e-complaint. Kata Kunci :Strategi Penerapan E-Government, Pelayanan Publik dan E-Complain